2019
DOI: 10.1177/0748730419851655
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium Regulates the Circadian Oscillator in Cyanobacteria

Abstract: The circadian clock controls 24-h biological rhythms in our body, influencing many time-related activities such as sleep and wake. The simplest circadian clock is found in cyanobacteria, with the proteins KaiA, KaiB, and KaiC generating a self-sustained circadian oscillation of KaiC phosphorylation and dephosphorylation. KaiA activates KaiC phosphorylation by binding the A-loop of KaiC, while KaiB attenuates the phosphorylation by sequestering KaiA from the A-loop. Structural analysis revealed that magnesium r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 32 publications
(52 reference statements)
0
27
0
Order By: Relevance
“…Daily magnesium fluxes are thought to regulate cellular timekeeping and energy balance [37]. Intracellular magnesium concentration acts as a cell-autonomous timekeeping component to determine key clock properties in human cell lines and unicellular alga [38]. In addition, magnesium has an essential role in ion transport and electrical conductivity, which facilitate N-methyl-D-aspartic acid (NMDA) receptor function, an important sleep regulator [36].…”
Section: Discussionmentioning
confidence: 99%
“…Daily magnesium fluxes are thought to regulate cellular timekeeping and energy balance [37]. Intracellular magnesium concentration acts as a cell-autonomous timekeeping component to determine key clock properties in human cell lines and unicellular alga [38]. In addition, magnesium has an essential role in ion transport and electrical conductivity, which facilitate N-methyl-D-aspartic acid (NMDA) receptor function, an important sleep regulator [36].…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we suggested that altering the magnesium concentration may be a signal for entrainment of the circadian clock (Jeong et al, 2019). To determine whether the magnesium concentration changes in response to light and dark in cyanobacteria, we measured the total magnesium concentration through ICP-MS.…”
Section: Magnesium Ion Is Not Used As a Signal For Entrainment In Cyamentioning
confidence: 99%
“…The phosphorylation state of KaiC oscillates with a circadian period, and the structural basis of the mechanism is well known (Tseng et al, 2014;Tseng et al, 2017). KaiA and KaiB activate the autophosphorylation and autodephosphorylation of KaiC, respectively, by changing the A-loop conformation and the binding affinity of magnesium in KaiC (Chang et al, 2015;Jeong et al, 2019;Kim et al, 2008). These antagonistic interactions generate the rhythm of KaiC phosphorylation with a nearly 24-h period (Akiyama et al, 2008).…”
mentioning
confidence: 99%
“…The association of magnesium with sleep has been explored by other investigators [20,51]. Magnesium appears to have a role in sleep-wake cycles and act as a cell-autonomous timekeeping component [62,63]. It also plays a role in melatonin synthesis [64].…”
Section: Previous Studiesmentioning
confidence: 99%